Preclinical and Clinical Role of Coenzyme Q10 Supplementation in Various Pathological States - Rajesh, Kumar; Khan, M I; Mahesh, Prasad; Kumar, Srivastav Ritesh; Kumar, Srivastav Shiv (Drug Research, 2022)
Coenzyme Q10 (CoQ10) is an efficient antioxidant produced endogenously in a living organism. It acts as an important cofactor in the electron transport system of mitochondria and reported as a safe supplement in humans and animals with minimal adverse effect. CoQ10 is found naturally, as a trans configuration, chemical nomenclature of which is 2,3- dimethoxy-5- methyl-6-decaprenyle -1,4-benzoquinone. It is found in the body in two forms. In quinone form (oxidized form), it serves as an electron transporter that transfers the electrons in the electron transport chain between various complexes, and in ubiquinol form (reduced form), it serves as potent antioxidants by scavenging free radicals or by tocopherol regeneration in the living organism. Its primary roles include synthesis of adenosine triphosphate (ATP), stabilizes lipid membrane, antioxidant activity, cell growth stimulation, and cell death inhibition. CoQ10 has shown a variety of pharmacological and clinical effects including neuroprotective, hepatoprotective, anti-atherosclerotic, anticonvulsant, antidepressant, anti-inflammatory, antinociceptive, cardiovascular, antimicrobial, immunomodulatory, and various effects on the central nervous system. Present review has set about to bring updated information regarding to clinical and preclinical activities of CoQ10, which may be helpful to researchers to explore a new bioactive molecules for various therapeutic application.
Keywords: Antioxidants; Benzoquinone; Electron transporter; LD50; Cofactor